Calcium Signaling and Contractility in Cardiac Myocyte of Wolframin Deficient Rats - Cagalinec, Michal; Zahradníková, Alexandra; Zahradníková, Alexandra; Kováčová, Dominika; Paulis, Ludovit; Kureková, Simona; Hot’ka, Matej; Pavelková, Jana; Plaas, Mario; Novotová, Marta; Zahradník, Ivan (Frontiers in Physiology, 2019)
Wolframin (Wfs1) is a membrane protein of the sarco/endoplasmic reticulum. Wfs1 mutations are responsible for the Wolfram syndrome, characterized by diabetic and neurological symptoms. Although Wfs1 is expressed in cardiac muscle, its role in this tissue is not clear. We have characterized the effect of invalidation of Wfs1 on calcium signalling-related processes in isolated ventricular myocytes of exon5-Wfs1 deficient rats (Wfs1 e5/ e5) before the onset of overt disease. Calcium transients and contraction were measured in field-stimulated isolated myocytes using confocal microscopy with calcium indicator fluo3-AM and sarcomere length detection. Calcium currents and their calcium release-dependent inactivation were characterized in whole-cell patch-clamp experiments. At 4 months, Wfs1 e5/ e5 animals were euglycaemic, and echocardiographic examination revealed fully compensated cardiac function. In field-stimulated isolated ventricular myocytes, both the amplitude and the duration of contraction of Wfs1 e5/ e5 animals were elevated relative to control Wfs1+/+ littermates. Increased contractility of myocytes resulted largely from prolonged cytosolic calcium transients. Neither the amplitude of calcium currents nor their voltage dependence of activation differed between the two groups. Calcium currents in Wfs1 e5/ e5 myocytes showed a larger extent of inactivation by short voltage prepulses applied to selectively induce calcium release-dependent inactivation of calcium current. Neither the calcium content of the sarcoplasmic reticulum, measured by application of 20 mmol/l caffeine, nor the expression of SERCA2, determined form Western blots, differed significantly in myocytes of Wfs1 e5/ e5 animals compared to control ones. These experiments point to increased duration of calcium release in ventricular myocytes of Wfs1 e5/ e5 animals. We speculate that the lack of functional wolframin might cause changes leading to upregulation of RYR2 channels resulting in prolongation of channel openings and/or a delay in termination of calcium release.